Cultivating Digital Classrooms: Exploring Pakistani ESL Teachers’ ICT Knowledge and Attitudes towards ICT at the Graduate Level - Sattar, Maliha; Javed, Hafiz Muhammad Hammad; Zamir, Muhammad Ali (Pakistan Journal of Humanities and Social Sciences, 2023)
This empirical study aimed to investigate Pakistani ESL teachers' knowledge and their attitudes towards information and communication technology (ICT) integration in language classes. This study was descriptive and exploratory in nature. Mixed method of research was used to guarantee triangulation, including questionnaire and a semi-structured, face-to-face interview. Cronbach’s alpha (?) was implemented to check the reliability of the questionnaire, and a pilot study was conducted to evaluate the validity of the research questions. The teachers who have been teaching Graduate-level courses were included as the population of research. Data analyzed through SPSS indicated that 78.3% teachers were more comfortable with ICT as compared to traditional teaching methods. According to 71.7% of them, ICT works like a catalyst and speeds up the teaching learning process (TLP) and enhance learners’ level of interest. Their knowledge of technology, however, directly correlates with their positive attitudes towards ICT integration as 56.7% of the participants know internet browsing. Moreover, study suggests that knowledge is a crucial factor effecting ESL teachers’ attitude towards ICT use. Subsequently, they should be given training to promote learning through digital system (LDS).